Impact of door-to-balloon time on long-term mortality in high- and low-risk patients with ST-elevation myocardial infarction. (1st December 2016) - Yudi, Matias B.; Ramchand, Jay; Farouque, Omar; Andrianopoulos, Nick; Chan, William; Duffy, Stephen J.; Lefkovits, Jeffrey; Brennan, Angela; Spencer, Ryan; Fernando, Dharsh; Hiew, Chin; Freeman, Melanie; et al.
Abstract: Background: Door-to-balloon time (DTBT) less than 90 min remains the benchmark of timely reperfusion in ST-elevation myocardial infarction (STEMI). The relative long-term benefit of timely reperfusion in STEMI patients with differing risk profiles is less certain. Thus, we aimed to assess the impact of DTBT on long-term mortality in high- and low-risk STEMI patients. Method: We analysed baseline clinical and procedural characteristics of 2539 consecutive STEMI patients who underwent primary percutaneous coronary intervention (PCI) from the Melbourne Interventional Group registry from 2004 to 2012. Patients were classified high risk (HR-STEMI) if they presented with cardiogenic shock, out-of-hospital cardiac arrest (OHCA) or Killip class ≥ 2; or low-risk (LR-STEMI) if there were no high-risk features. We then stratified high- and low-risk patients by DTBT (≤ 90 min vs. > 90 min) and assessed long-term mortality. Result: Of the 2539 patients, 395 (16%) met the high-risk criteria. A DTBT ≤ 90 min was achieved in 43% of HR-STEMI patients and in 55% of LR-STEMI patients. Patients in the HR-STEMI compared to LR-STEMI cohort had higher in-hospital (31% vs. 1%, p  < 0.01) and long-term mortality (37% vs. 7%, p  < 0.01). A DTBT ≤ 90 min was associated with significant improvements in short- and long-term mortality in both groups. A DTBT ≤ 90 min was an independent multivariate predictor of long-term survival in LR-STEMI (hazard ratio [HR] 0.5, 95% confidence interval [CI] 0.3–0.9, p  = 0.02) but not in HR-STEMI (HR 0.7, 95% CI 0.5–1.1, p  = 0.11). Conclusion: A DTBT ≤ 90 min was associated with improved short- and long-term outcomes in high- and low-risk STEMI patients. However, it was only an independent predictor of long-term survival in LR-STEMI patients.